Fullerene patches II - Graver, Jack E. (Ars mathematica contemporanea, 2014)
In this paper, we show that fullerene patches with nice boundaries containing between 1 and 5 pentagons fall into several equivalence classes; furthermore, any two fullerene patches in the same class can be transformed into the same minimal configuration using combinatorial alterations.
Keywords: fulereni; fullerene patches; fullerenes; pseudoconvex patches; teorija grafov